Macrophage ALDH2 (Aldehyde Dehydrogenase 2) Stabilizing Rac2 Is Required for Efferocytosis Internalization and Reduction of Atherosclerosis Development. Issue 6 (31st March 2022) - Zhang, Jian; Zhao, Xiangkai; Guo, Yunyun; Liu, Zhiping; Wei, Shujian; Yuan, Qiuhuan; Shang, Haixia; Sang, Wentao; Cui, Sumei; Xu, Tonghui; Yang, Kehui; Guo, Jialin; et al.
Abstract : Background: Clinical studies show that the most common single-point mutation in humans, ALDH2 (aldehyde dehydrogenase 2) rs671 mutation, is a risk factor for the development and poor prognosis of atherosclerotic cardiovascular diseases, but the underlying mechanism remains unclear. Apoptotic cells are phagocytosed and eliminated by macrophage efferocytosis during atherosclerosis, and enhancement of arterial macrophage efferocytosis reduces atherosclerosis development. Methods: Plaque areas, necrotic core size, apoptosis, and efferocytosis in aortic lesions were investigated in APOE −/− mice with bone marrow transplanted from APOE − /− ALDH2 − /− and APOE − /− mice. RNA-seq, proteomics, and immunoprecipitation experiments were used to screen and validate signaling pathways affected by ALDH2. Efferocytosis and protein levels were verified in human macrophages from wild-type and rs671 mutation populations. Results: We found that transplanting bone marrow from APOE − /− ALDH2 − /− to APOE − /− mice significantly increased atherosclerosis plaques compared with transplanting bone marrow from APOE − /− to APOE − /− mice. In addition to defective efferocytosis in plaques of APOE − /− mice bone marrow transplanted from APOE − /− ALDH2 − /− mice in vivo, macrophages from ALDH2 − /− mice also showed significantly impaired efferocytotic activity in vitro. Subsequent RNA-seq, proteomics, and immunoprecipitation experiments showed that wild-type ALDH2 directly interacted with Rac2 and attenuated its degradation due to decreasing the K48-linked polyubiquitination of lysine 123 in Rac2, whereas the rs671 mutant markedly destabilized Rac2. Furthermore, Rac2 played a more crucial role than other Rho GTPases in the internalization process in which Rac2 was up-regulated, activated, and clustered into dots. Overexpression of wild-type ALDH2 in ALDH2 − /− macrophages, rather than the rs671 mutant, rescued Rac2 degradation and defective efferocytosis. More importantly, ALDH2 rs671 in human macrophages dampened the apoptotic cells induced upregulation of Rac2 and subsequent efferocytosis. Conclusions: Our study has uncovered a pivotal role of the ALDH2-Rac2 axis in mediating efferocytosis during atherosclerosis, highlighting a potential therapeutic strategy in cardiovascular diseases, especially for ALDH2 rs671 mutation carriers.